Peran Kepuasan Kerja, Motivasi Kerja, dan Disiplin Kerja Terhadap Kinerja Karyawan : Studi Empiris CV Sukses Abadi Garmandio - Shukuria Birgita Lelis Inggarwati; Heni Susilowati (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2026)
Human Resources (HR) is a strategic component in an organization, as employees' roles will support the overall success of the organization. The purpose of this study is to analyze the influence of job satisfaction, work motivation, and work discipline on employee performance at CV Sukses Abadi Garmindo. This study uses a quantitative survey approach using primary data sources. The sampling technique used a simple random sampling method with the Slovin formula for 84 respondents. Data were analyzed using multiple linear regression. The results show that job satisfaction has no significant effect on employee performance. Meanwhile, work motivation and work discipline have a significant effect on employee performance at CV Sukses Abadi Garmindo. Management needs to pay attention to incentive and welfare systems as motivation in improving employee performance.